Preeklampsia Berat dan Infeksi HIV pada Primigravida Usia Kehamilan 37 Minggu: Sebuah Laporan Kasus - Daraz, Fadila Gustiani; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2024)
The three main causes of maternal death in obstetric fields are: bleeding, hypertension in pregnancy, and infection. Severe preeclampsia is hypertension that appears at 20 weeks of pregnancy with accompanying organ disorders. HIV infection during pregnancy can cause vertical transmission from mother to child both during pregnancy and during labor. This case report discusses a primigravida woman in 37 weeks' gestation, with the chief complaints of about to give birth with HIV positive, there is no history of hypertension before pregnancy. Patient's physical examination showed fully conscious, blood pressure 161/112 mmHg, pulse frequency 112 x/minute, breathing frequency 20 x/minute, temperature 36.5ºC. Generalized status is obtained within normal limits. On obstetric examination, TFU is 39 cm, the uterus contracts with a frequency of 3 times in 10 minutes and a duration of 30 seconds, fetal heart rate 131 x/minute and 135 x/minute. Ultrasound examination is obtained by a double fetus. Patients undergo blood tests and obtained hemoglobin value 11.7 gr/dl, leukocytes 6,800/μl, hematocrit 33%, platelets 285,000/μl, AST 18 U/L, ALT 7 U/L, Ureum 18 mg/dl, creatinine 0 , 68 mg/DL and LDH 326 U/L. On urinalysis 150 protein (++). On immunological and serological examinations, HIV positive results were obtained. Management for this patient is observation of vital signs, uterine contractions, fetal heart rate, 1-3 hours stabilization, catheter installation permits with input/output recording. Medications were given to the patient including RL 20 drops/minute, 4 grams MgSO4 40% then drip 6 gram MgSO4 40% in RL 500 cc 10 drops/minutes, nifedipine orally 3x10mg, and injection of dexamethasone 10mg/12 hours, ARV medicine and performed termination of pregnancy by caesaria section. Childbirth through caesaria section surgery is at a less risk for transmission to infants, but adds other risks to the mother. Good, intraoperative, and postoperative preoperative management will make this caesaria section successful without obstacles.